From settlers to subspecies: Genetic differentiation in Commerson’s dolphins between South America and the Kerguelen Islands - Poulin, Elie; Kraft, Sebastián; Olavarría, Carlos; Moraga, Rodrigo; Baker, C. Scott; Steel, Debbie; Tixier, Paul; Guinet, Christophe; Brickle, Paul; Viricel, Amelia; Costa, Marina; Crespo, Enrique Alberto; et al.
The Commerson´s dolphin Cephalorhynchus commersonii is divided into two subspecies, C. c. commersonii from southern South America and the Falklands/Malvinas and C. c. kerguelenensis, restricted to the subantarctic Kerguelen Islands. Following the West to East diversification model proposed for the genus, the latter subspecies is thought to have originated from a long distance dispersal event from South America. In order to improve the evaluation of this biogeographic scenario, new samples from southern Chile (n=6) and Kerguelen (n=23) were added to previously published mtDNA control region sequences from Patagonia (n=292) and Kerguelen (n=11). Moreover, 52 samples from Falklands/Malvinas were included, adding a new area to complete the whole distribution range of the species. Significant phylogeographic structure was found among the three areas, being much higher between Kerguelen and southern South America (including Falklands/Malvinas, SA-FI range Φst=0.44-0.51) than between Patagonia and Falklands/Malvinas (Φst=0.11-0.14). Using the genetic data, the proposed historical biogeographic scenario of colonization was tested with Approximate Bayesian Calculations. Initial trials show that the dispersal event from South America to Kerguelen Island may have occurred in the early Holocene and was followed by a population expansion process in Kerguelen Island. These results support the model of postglacial colonization of Kerguelen by South American C. commersonii followed by a still ongoing differentiation process. Fil: Poulin, Elie. Universidad de Santiago de Chile. Facultad de Ciencias; Chile Fil: Kraft, Sebastián. No especifíca; Fil: Olavarría, Carlos. Comisión Nacional de Investigación Científica y Tecnológica. Centro de Investigación Regional. Centro de Estudios en Zonas Áridas; Chile Fil: Moraga, Rodrigo. Centro de Investigación Eutropia; Chile Fil: Baker, C. Scott. University of Oregon; Estados Unidos Fil: Steel, Debbie. University of Oregon; Estados Unidos Fil: Tixier, Paul. Centre National de la ...